Minimally invasive strategies and options for far-lateral lumbar disc herniation - 周跃 张超 王建 初同伟 李长青 张正丰 郑文杰 (Chinese journal of traumatology, 2008)
Objective： To investigate the surgical procedures, options and surgical indications for far-lateral lumbar disc herniation between three different minimally invasive procedures. Methods： From January 2000 to October 2006, 52 patients with far-lateral lumbar disc herniation （29 males and 23 females, with the average age of 41.5 years） were treated with minimally invasive procedures. All the patients were assessed by X-ray and CT. Some were given additional myeography, discography, Computerized tomography myelography （CTM） and MRI examination. Yeung Endoscopy Spine System （YESS）, METRx and X-tube procedures were performed in 25, 13 and 14 cases, respectively. All patients were followed up for a mean period of 13.5 months. Clinical outcomes were assessed by visual analog score （VAS） and Nakai criteria. Results： The results indicated that the three procedures could significantly improve the radiating leg symptoms （P〈0.05）. The postoperative overall excellent and goodrates of YESS, METRx and X-tube procedures were 84.0%, 84.6% and 92.8% respectively, with no statistical difference among three groups （P〉0.05）. The YESS procedure had several advantages including shortest operation time, simplest anesthesia and least trauma as compared with the other two procedures, especially for simple type I far-lateral lum- bar disc herniation. METRx procedure was specially suitable for simple type II. And the procedure of posterior endoscopic facetectomy, posterior lumbar interbody fusion and unilateral pedicle screw instrumentation with X-tube was designed for far-lateral disc herniation combined with degenerative lumbar instability. Conclusion： Minimally invasive strategies and options should be determined by different types of far-lateral lumbar disc herniation.